Community health workers and Covid-19: Cross-country evidence on their roles, experiences, challenges and adaptive strategies - Salve, Solomon; Raven, Joanna; Das, Priya; Srinivasan, Shuchi; Khaled, Adiba; Hayee, Mahwish; Olisenekwu, Gloria; Gooding, Kate (PLOS global public health, 2023)
Community health workers (CHWs) are a key part of the health workforce, with particular importance for reaching the most marginalised. CHWs’ contributions during pandemics have received growing attention, including for COVID-19. This paper contributes to learning about CHWs’ experiences during COVID-19, based on evidence from India, Bangladesh, Pakistan, Sierra Leone, Kenya and Ethiopia. The paper synthesises evidence from a set of research projects undertaken over 2020–2021. A thematic framework based on the research focus and related literature was used to code material from the reports. Following further analysis, interpretations were verified with the original research teams. CHWs made important contributions to the COVID-19 response, including in surveillance, community education, and support for people with COVID-19. There was some support for CHWs’ work, including training, personal protective equipment and financial incentives. However, support varied between countries, cadres and individual CHWs, and there were significant gaps, leaving CHWs vulnerable to infection and stress. CHWs also faced a range of other challenges, including health system issues such as disrupted medical supply chains, insufficient staff and high workloads, a particular difficulty for female CHWs who were balancing domestic responsibilities. Their work was also affected by COVID-19 public health measures, such as restrictions on gatherings and travel; and by supply-side constraints related to community access and attitudes, including distrust and stigmatization of CHWs as infectious or informers. CHWs demonstrated commitment in adapting their work, for example ensuring patients had adequate drugs in advance of lockdowns, and using their own money and time to address increased transport costs and higher workloads. Effectiveness of these adaptations varied, and some involved coping in a context of inadequate support. CHW are critical for effective response to disease outbreaks, including pandemics like COVID-19. To support CHWs’ contribution and protect their wellbeing, CHWs need adequate resources, managerial support, and motivation.